Morpho‐regulation in diverse chicken feather formation: Integrating branching modules and sex hormone‐dependent morpho‐regulatory modules. (19th December 2018) - Widelitz, Randall B.; Lin, Gee‐Way; Lai, Yung‐Chih; Mayer, Julie A.; Tang, Pin‐Chi; Cheng, Hsu‐Chen; Jiang, Ting‐Xin; Chen, Chih‐Feng; Chuong, Cheng‐Ming
Abstract: Many animals can change the size, shape, texture and color of their regenerated coats in response to different ages, sexes, or seasonal environmental changes. Here, we propose that the feather core branching morphogenesis module can be regulated by sex hormones or other environmental factors to change feather forms, textures or colors, thus generating a large spectrum of complexity for adaptation. We use sexual dimorphisms of the chicken to explore the role of hormones. A long‐standing question is whether the sex‐dependent feather morphologies are autonomously controlled by the male or female cell types, or extrinsically controlled and reversible. We have recently identified core feather branching molecular modules which control the anterior‐posterior (bone morphogenetic orotein [BMP], Wnt gradient), medio‐lateral (Retinoic signaling, Gremlin), and proximo‐distal (Sprouty, BMP) patterning of feathers. We hypothesize that morpho‐regulation, through quantitative modulation of existing parameters, can act on core branching modules to topologically tune the dimension of each parameter during morphogenesis and regeneration. Here, we explore the involvement of hormones in generating sexual dimorphisms using exogenously delivered hormones. Our strategy is to mimic male androgen levels by applying exogenous dihydrotestosterone and aromatase inhibitors to adult females and to mimic female estradiol levels by injecting exogenous estradiol to adult males. We also examine differentially expressed genes in the feathers of wildtype male and female chickens to identify potential downstream modifiers of feather morphogenesis. The data show male and female feather morphology and their color patterns can be modified extrinsically through molting and resetting the stem cell niche during regeneration. Abstract : We propose that feather morphogenesis modules can be regulated by sex hormones or other environmental factors to change feather forms, textures or colors, thus generating a large spectrum of complexity for adaptation. We examine the roles of sex hormones in avian feather sexual dimorphisms by mimicking male androgen levels in female chickens and female androgen levels in males. We also examine differentially expressed genes in wildtype male and female chickens to identify potential downstream modifiers of feather morphogenesis.